DAMPAK PENGELOLAAN SUMBER DAYA ALAM MIGAS TERHADAP PEMBANGUNAN DAERAH DAN IMPLIKASINYA PADA KETAHANAN WILAYAH (Studi Pada Masyarakat Sekitar Pertambangan Migas Di Kabupaten Bojonegoro) - , ELLY IRHANA SAVITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cepu block is a regional contract of oil and natural gas which consist of Bojonegoro Regency â East Java, Blora Regency â central java, and Tuban Regency â East java with most of its working are in Bojonegoro Regency. The oil and gas exploration will affect the environment from the preparation to the post drilling process. It will change the soil shape because of the drilling, soil flattening and compaction. The activity will also change agricultural filed into drilling field. The once green location will turn into a arid and barren field and it will decrease the air quality due to the vehicle heavy vehicles mobility in the project area. The researchâs purpose is to study oil and gas natural source management system in Bojonegoro Regency which will include the revenue-sharing (DBH) distribution relate to the regional development as mention in the regional law and regulation. It will focus on physical environment, social culture environment and development aspects. The research process started with literature study, and then field visual observation, documentation, questionnaire, and interview to the related parties of the reference on this research. The result of this research shows the oil and gas natural source management implementation due to the revenue â sharing is operating as the regulation. The environmental impact on air quality, agricultural field, health, and communities hygienic is not on significance risk. The recommendation on the physical environment is the greening on the mine location, observation and evaluation of environmental impact periodically